Capacitação estratégica, política de atendimento e desempenho em serviços de hospedagem nas micro e pequenas empresas na cidade de Salvador - Carrera, Luiz Carlos Seoane (2004)
The general goal of this work is to mark the profile of the micro and small companies manager from the segment of hostelry in Salvador-Bahia, identifying aspects that can justify the currently observed deficiencies at the attendance, hygiene, storage and manipulation of food. It is necessary to draw attention to the importance of the analyses of the employers profile, once he s the one who set the rules of his establishment, noticing the fact that only with good training, of the owner as well as of the employees, it will be possible to promote improvements at the management of the company, resulting in better service and consequently, in better performance.